NifU and NifS are required for the maturation of nitrogenase and cannot replace the function of isc-gene products in Azotobacter vinelandii. (1st February 2005) - Johnson, D.C.; Dos Santos, P.C.; Dean, D.R.
Abstract : In recent years, it has become evident that [Fe-S] proteins, such as hydrogenase, nitrogenase and aconitase, require a complex machinery to assemble and insert their associated [Fe-S] clusters. So far, three different types of [Fe-S] cluster biosynthetic systems have been identified and these have been designated nif, isc and suf . In the present work, we show that the nif -specific [Fe-S] cluster biosynthetic system from Azotobacter vinelandii, which is required for nitrogenase maturation, cannot functionally replace the isc [Fe-S] cluster system used for the maturation of other [Fe-S] proteins, such as aconitase. The results indicate that, in certain cases, [Fe-S] cluster biosynthetic machineries have evolved to perform only specialized functions.